Contributions of Pulsed Operation Along with Proper Choice of the Substrate for Stabilizing the Catalyst Performance in Electrochemical Reduction of CO2 Toward Ethylene in Gas Diffusion Electrode Based Flow Cell Reactors. Issue 7 (14th May 2022) - Jännsch, Yannick; Hämmerle, Martin; Simon, Elfriede; Fleischer, Maximilian; Moos, Ralf
Abstract : Electrochemical reduction of CO2 is a promising method to close the carbon cycle and thereby contribute to counteracting climate change. A large share of the research is going into the development of new high‐performance catalysts. Often, these catalysts are expensive and difficult to synthesize, especially if considering scaling up to the industrial application. The catalyst is, however, only one factor within the complex system of a CO2 ‐electrolyzer with numerous parameters to explore and optimize. Herein, an optimization process relying on a commercial copper nanopowder as a catalyst is reported. By replacing conductive carbon with polytetrafluoroethylene as the base material of the gas diffusion electrode (GDE) and applying a pulsed potential during electrolysis, the average faradaic efficiency for ethylene could be increased from 38% over 20 h to 50% over 100 h. In addition to the five times increased stability of the process, the ethylene‐producing current density rises from 106 to 152 mA cm −2, respectively, while hydrogen evolution was simultaneously reduced. Additionally, further investigations on the interplay of GDE base material, binder, current collector, and catalyst on the electrode performance are presented. Abstract : In this study, the selectivity and stability of the CO2 ‐reduction toward ethylene using gas diffusion electrodes was optimized. Therefore, the different layers of the electrode were tailored to their individual task. Together with a pulsed potential, a faradaic efficiency of 50% and a current density of 152 mA cm −2 for ethylene were reached, averaged over 100 h of operation.